Obesity, sex and pubertal status affect appetite hormone responses to a mixed glucose and whey protein drink in adolescents. (30th January 2014) - Patel, Barkha P.; Anderson, G. Harvey; Vien, Shirley; Bellissimo, Nick; McCrindle, Brian W.; Hamilton, Jill K.
Summary Background and Objectives Little information is available on how food intake regulatory hormones may be altered during pubertal development and across the weight spectrum in adolescents. Therefore, the effect of obesity, sex and pubertal status on subjective appetite and appetite hormones in response to a mixed glucose and whey protein drink was determined in 8–18 year old adolescents. Patients and Methods A cross‐sectional cohort study was conducted at the Hospital for Sick Children, Toronto. After a 12 h fast, normal weight (n = 5 female, 4 male) and obese (n = 5 female, 4 male) adolescents (Experiment 1), and pre‐early pubertal (n = 10) and mid‐late pubertal (n = 10) obese male adolescents (Experiment 2) consumed a 250 ml glucose (30 g) and whey protein (30 g) beverage. Insulin, PYY, ghrelin and subjective appetite were measured over 120 min. Results Obese adolescents (Experiment 1) have higher insulin, PYY and lower ghrelin (P < 0·006) than normal weight controls, with a more pronounced effect in males (P < 0·037). Puberty (Experiment 2) did not affect insulin (P = 0·305), but the change in PYY in response to the drink was greater (P = 0·032) and ghrelin was lower (P = 0·026) in mid‐late pubertal than pre‐early pubertal obese males. Average appetite 60 min post‐drink was higher in obese and mid‐late pubertal adolescents, but not related to hormone changes. Conclusions Obesity, sex and pubertal status affect macronutrient‐stimulated appetite hormone secretion and these factors may alter food intake in obese children during pubertal development.